2003
DOI: 10.1002/jcb.10375
|View full text |Cite
|
Sign up to set email alerts
|

IRES‐dependent translational control of Cbfa1/Runx2 expression

Abstract: The P1 and P2 promoters of the Cbfa1/Runx2 gene produce Type I and II mRNAs with distinct complex 5'-untranslated regions, respectively designated UTR1 and UTR2. To evaluate whether the 5'-UTRs impart different translational efficiencies to the two isoforms, we created SV40 promoter-UTR-luciferase reporter (luc) constructs in which the translational potential of the 5'-UTR regions was assessed indirectly by measurement of luciferase activity in transfected cell lines in vitro. In MC3T3-E1 pre-osteoblasts, UTR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…The mouse lck proximal promoter was required for tissue-specific expression in the thymus and mtβ was a critical transactivator for the proximal promoter (Reynolds et al, 1990;Yamada et al, 2001). The phenomenon of a differential expression pattern from a single gene by alternative promoters is very common, and is often related to tissuespecific expression of that gene (Christophi et al, 2004;Hai et al, 2001;Jian et al, 2006;Tao et al, 2001;Xiao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The mouse lck proximal promoter was required for tissue-specific expression in the thymus and mtβ was a critical transactivator for the proximal promoter (Reynolds et al, 1990;Yamada et al, 2001). The phenomenon of a differential expression pattern from a single gene by alternative promoters is very common, and is often related to tissuespecific expression of that gene (Christophi et al, 2004;Hai et al, 2001;Jian et al, 2006;Tao et al, 2001;Xiao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that Runx2 expression can be modulated in several ways, including direct stimulation of gene expression, post-translational modification, and proteinprotein interactions (Li et al, 2004b;Bae and Lee, 2006;Shen et al, 2006). It is known that Runx2 mRNA can be translated by capdependent and cap independent internal ribosomal entry site (IRES) mechanisms (Xiao et al, 2003;Elango et al, 2006;Nishio et al, 2006). IRES-dependent translation adds an additional level at which expression of this gene is regulated.…”
Section: Discussionmentioning
confidence: 99%
“…DNase I-treated total RNA (1.0 g) was reverse-transcribed into cDNA with the reverse primer described before (44). The reverse transcription reaction was incubated at 50°C for 30 min.…”
Section: Measurement Of Alkaline Phosphatase Activity and Mineralizatmentioning
confidence: 99%
“…Equal quantities of protein were subjected to NuPAGE TM 4 -12% Bis-Tris gel (Invitrogen) and were analyzed with standard Western blot protocols (horseradish peroxidase-conjugated secondary antibodies from Santa Cruz Biotechnology and ECL from Amersham Biosciences). RUNX2 (sc-10758) and lamin A/C (sc-6215) antibodies from Santa Cruz Biotechnology were used according to the manufacturer's instructions (44).…”
Section: Real-time Rt-pcr and Westernmentioning
confidence: 99%